A pin-array method for capturing tissue deformation under defined pressure distributions and its application to prosthetic socket design. (October 2020) - Prince, Michael; Kenney, Laurence PJ; Howard, Dave
Highlights: A tool using a pin-array can apply a chosen pressure distribution to tissue. Clamping the pins allows the shape of the loaded tissue to be captured. The tool could be useful in designing components which apply desired loads at the skin surface. Abstract: The Fit4Purpose project aims to develop upper limb prosthetic devices which are suitable for deployment in lower- and middle-income countries (LMIC's). Open-frame trans-radial socket designs are being considered, formed of several, linked components, including pads which interface directly with the skin surface. A mechanical tool has been developed to aid the design of pad shapes, using an array of square brass bars of varying lengths (i.e. a pin-array) to apply a chosen normal pressure distribution to an area of tissue. The shape to which the tissue is displaced can then be captured by clamping the bars together to fix their relative positions. The device is described, then three short studies are used to demonstrate its use on the forearm of a single, anatomically intact subject. The first investigates the effect of array size on the measured surface stiffness, finding an inverse relationship with a similar characteristic to previous published results. The second tests the hypothesis that a pad with a shape which duplicates that captured by the device will generate a similar overall load to the original pins if applied to the same region of tissue. The results support the hypothesis, but also highlight the sensitivity of the interface loading to the underlying muscle activation. Finally, the tool is used to demonstrate that different tissue displacements are observed when the same pressure distribution is applied to different areas of the forearm. Whilst the tool itself is a simple device, and the techniques used are not sophisticated, the studies suggest that the approach could be useful in pad design. Although it is clearly not appropriate for clinical application in its current form, there may be potential to develop the concept into a more practical device. Other applications could include the design of other devices which interface with the skin, the generation of data for validation of finite element models, including the application of known pressure distributions and tissue deformations during Magnetic Resonance Imaging, and the assessment of matrix pressure sensing devices on compliant materials with complex geometries.